2016
DOI: 10.3390/rs8110940
|View full text |Cite
|
Sign up to set email alerts
|

Deriving and Evaluating City-Wide Vegetation Heights from a TanDEM-X DEM

Abstract: Vegetation provides important functions and services in urban areas, and vegetation heights divided into vertical and horizontal units can be used as indicators for its assessment. Conversely, detailed area-wide and updated height information is frequently missing for most urban areas. This study sought to assess three vegetation height classes from a globally available TanDEM-X digital elevation model (DEM, 12 × 12 m spatial resolution) for Berlin, Germany. Subsequently, height distribution and its accuracy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The true scatter center of the X-band wave should be somewhat lower than 79% of true canopy height, because the LiDAR DSM also provides a slight underestimate of canopy height [51]. The underestimation of canopy heights by TDX DEM is not confined to mangrove forests, but also occurs in many other types of forest, including tropical peat swamp, patchy savanna, boreal, and urban forests [21,[23][24][25]. Both Balzter et al [21] and Sadeghi et al [24] demonstrated that the TDX DEM elevations were located between the LiDAR DTM and DSM elevations in patchy savanna and boreal forests.…”
Section: Forested Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The true scatter center of the X-band wave should be somewhat lower than 79% of true canopy height, because the LiDAR DSM also provides a slight underestimate of canopy height [51]. The underestimation of canopy heights by TDX DEM is not confined to mangrove forests, but also occurs in many other types of forest, including tropical peat swamp, patchy savanna, boreal, and urban forests [21,[23][24][25]. Both Balzter et al [21] and Sadeghi et al [24] demonstrated that the TDX DEM elevations were located between the LiDAR DTM and DSM elevations in patchy savanna and boreal forests.…”
Section: Forested Areamentioning
confidence: 99%
“…The TDX DEM dataset provides a consistent and global source for estimating the elevations of terrain, vegetation, and buildings by covering all of the Earth's surface at least twice during the mission [12,18].In 2014, the DLR released the intermediate TDX DEM (IDEM) data to the scientific community for experimental research, based on the first-pass of the TDX DEM mission [19]. The IDEMs were subsequently verified by ICESat, airborne LiDAR and GPS measurements at many study sites [20][21][22][23] and have been used to map canopy heights of boreal forests [24], urban tree heights [25], and building heights [26]. In 2016, the DLR released the final TDX DEM product to the scientific community [27].…”
mentioning
confidence: 99%
“…This approach was rarely exploited to date e.g. [6]. Given that TanDEM-X DEM represents a DSM, for geomorphologic studies, it is crucial to analyse its semantic accuracy of identification of landforms associated with the terrain surface.…”
Section: Introductionmentioning
confidence: 99%
“…TanDEM-X mission is designed to generate a global DEM with unprecedented accuracy [13] as the basis for 2 Journal of Sensors various applications, such as landslide tracking [14], glacier changing [15][16][17], vegetation evaluating [18,19], lava flow estimating [20,21], and permafrost monitoring [22]. The TanDEM-X mission consists of twin satellites TerraSAR-X and TanDEM-X working on bistatic interferometry mode, which is characterized by the illumination of a target region on the ground by one transmitter and the simultaneous acquisition of the backscattered signals with two receivers [23].…”
Section: Introductionmentioning
confidence: 99%